Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Agama Islam - Upe, Asrizal A.; Sukandar, Ahmad; Setiawan, Marwan (Edukasi: Journal of Educational Research, 2021)
Human nature is a social creature which according to Aristotle is called the "Zoon Politicon". In an effort to socialize, humans or humans enter a group or organization, then when something emerges, recognizes the advantages and influences and drives joint efforts in achieving a predetermined goal, then he is called a leader. This research uses an organization that is a school educational institution. Educational leaders must have a commitment to quality improvement in their main functions. Therefore, the functions of educational leadership must be directed at the quality or quality of learning. The quality of education is a direct consequence of a change and development of various aspects of life. There are various styles of heads in implementing and developing leadership activities, namely authoritarian leadership style, Laissez Faire leadership style, democratic leadership style. On that basis, this research is focused on the limitations of the problem in this study, there are two, namely: 1) How is the Quality of Islamic Religious Education at SMA Negeri 1 Ciwidey?; and 2) How is the principal's leadership style in improving the quality of Islamic religious education in educational institutions. Furthermore, this study uses qualitative research methods using a case study plan on the leadership style of school principals in improving the quality of Islamic religious education. The results of this study indicate that (1) the quality of Islamic education in SMA Negeri 1 Ciwidey can be said to be quite good, this can be seen in terms of input, process and output. In terms of input, the students of SMA Negeri 1 Ciwidey have the motivation to always improve themselves in achieving according to their talents and abilities, teachers, staff, TU, counselors and administrators who have expertise in their fields and are also supported by adequate facilities and infrastructure. In terms of process, Islamic religion teachers at SMA Negeri 1 Ciwidey have used various teaching methods so that it is easy for students to understand PAI material. In terms of output, most of the graduate students are accepted in top universities, are diligent in praying and can read the Qur'an. (2) The Leadership Style of the Principal of SMA Negeri 1 Ciwidey in improving the quality of Islamic religious education is more likely to use a (participatory) leadership style. In this case, the principal prioritizes deliberation and consensus in solving a problem. However, often in certain situations, the principal requires another (authoritarian).